If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 162 = 2xsquared Solving 162 = 2adeqrsux Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2adeqrsux' to each side of the equation. 162 + -2adeqrsux = 2adeqrsux + -2adeqrsux Combine like terms: 2adeqrsux + -2adeqrsux = 0 162 + -2adeqrsux = 0 Add '-162' to each side of the equation. 162 + -162 + -2adeqrsux = 0 + -162 Combine like terms: 162 + -162 = 0 0 + -2adeqrsux = 0 + -162 -2adeqrsux = 0 + -162 Combine like terms: 0 + -162 = -162 -2adeqrsux = -162 Divide each side by '-2deqrsux'. a = 81d-1e-1q-1r-1s-1u-1x-1 Simplifying a = 81d-1e-1q-1r-1s-1u-1x-1
| 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 | | 2cosx+4sinx=3 | | 16x-5y=125 | | 2y-4=29 | | y^2+11y+49=4 | | x((3x-3)(2x-8)+(2x+2)(3x+1))=(5x-5)(3x+1)(2x-8) | | ln(x)=-x+2 | | x^2+y^2-2y=3 | | 20log(3x)=49 | | 4.5=4.125 | | X^2+11X-450=0 | | 3x^4/x^2-9 | | 18(6)+x=134 | | 2x^2-4y-1=0 | | a=3.14(x+y)2 |